Telaah Teks Hadis tentang Jual Beli Emas Secara Tunai dan Kredit - Abdul Rahman Sakka (Sekolah Tinggi Agama Islam (STAI) Al-Azhar Gowa, 2021)
The pros and cons of public toward the DSN-MUI fatwa that allows the sale and purchase of gold on credit is inseparable from how to understand the text of the hadith. Therefore, it is necessary to carry out a research on hadith as it has been a source of law. This research focuses on the study of hadith texts on the sale and purchase of gold with external and internal criticism methods. External criticism is intended to confirm the status of the hadith, while internal criticism uses contextual interpretation to understand the content of the hadith. In the process of research, it was found that the hadith, which relates to the sale and purchase of gold has many chains so that it is categorized as a famous hadith quantitatively, while in quality it is defined as an authentic hadith. There are two versions of Muslim scholars in understanding the hadith of selling and purchasing gold as the result of ijtihad among the scholars in understanding the hadith. The first version is to restrict the sale and purchase of gold with money, yet it can only be done in cash and to prohibit the sale and purchase of golf on credit according to the appearance of the hadith because gold and money have the same ‘illat ribawi although they are different in type. The second version is to allow the sale and purchase of gold in cash and credit because gold has changed its status from money to goods like any other goods, so that ‘illat gold as a currency requiring cash transactions fall by itself.